RELATIONSHIP BETWEEN ADSORPTION-RHEOLOGICAL PROPERTIES OF SERUM IN HEMORRHAGIC VASCULITIS AND ECOLOGY IN REGIONS OF PATIENTS’ RESIDENCE - T.B. Bevzenko; I.Yu. Golovach; M. V. Yermolaieva; V.Ya. Mikuksts; O.V. Syniachenko (Проблеми екології та медицини)
The aim of the work: to assess the physic-chemical adsorption and rheological properties of the blood serum of patients with hemorrhagic vasculitis (HV) according to the hygienic condition of the air, water and soil in regions of patients residence. Materials and methods. The study involved 144 patients with HV (56% of men and 44% women with the average age 26 years). Indicators of surface viscosity (SV), bulk viscosity (BV), surface elasticity (SE), module of viscoelasticity (MV), relaxation time (RT), the surface tension at t = 0,01 sec (ST1) , t = sec 1 (ST2), t = 100 sec (ST3), and the equilibrium (static) surface tension at t (ST4), the angle of inclination (AI) and phasic angle (PA) of tensiograms were studied using computer tensioreometry of serum, surfactant criterion of interfacial activity (SCIA) were calculated. The results were compared with environmental pollution by xenobiotics and microelements of air, water and soil of zones of patients residence. Results and discussion. Adsorption-rheological properties of serum of patients with HV depend on the integrated degree of pollution by xenobiotics of air and drinking water (but not of soil by chemical elements), the degree of emissions and accumulation of industrial waste in it, the nature of the impact of modernization of agriculture, metallurgical, chemical and engineering industries in the regions, levels of 3,4-benzpyrene (ST2, PA), phenol (BV, PA), ammonia (SCIA), nitrogen dioxide (ST1, ST2, ST3), carbon dioxide (SE, RT, ST1, ST2, ST4) in the breathing air, the degree of mineralization and hardness of drinking water (MV), the parameters of toxic microelements and essential zinc (ST3) in the soil. Conclusions. Breach of the adsorption-rheological properties of blood serum in HV depend on hygienic condition of air, water and soil in regions of patients residence, the environmental burden on the atmosphere by the different branches of industry and agriculture.